The Right to Education of Vulnerable Groups of Children in the Russian Federation in the Light of the Activities of the UN Committee on the Rights of the Child - ABASHIDZE, Aslan; KISELEVA, Ekaterina; ILYASHEVICH, Marianna; NIKOLAEV, Andrey; BELOUSOVA, Anastasia (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9 3(33).01, 2018)
The right to education is enshrined in a number of international treaties to which Russia has acceded. As applicable to the right to education for children, the Convention on the Rights of the Child of 1989 holds a central position. The Russian Federation fulfills its obligations under Art. 44 CRC on the provision of periodic reports in good faith and has so far submitted five such reports. The analysis of the consideration of reports by the Committee on the Rights of the Child makes it possible to identify a number of categories of children who have particular difficulties with the exercise of the right to education. This article analyzes the problems of certain categories of children in the Russian Federation with regard to the right to education and suggests specific recommendations for improving the situation.